an J Health Educ Health Promot 2019
DOI: 10.30699/ijhehp.7.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Emotion Regulation Training Based on Grass Model on Reducing Rumination and Social Anxiety in Female Students with 60-Day Follow-up

Abstract: Background and Objectives: Social anxiety and rumination are one of the most common emotional problems which affect the lives of different groups, especially young people. The aim of the present study is to examine the effect of emotion regulation training on reducing the rumination and social anxiety of second high school girl students in Shahrekord. Methods: The research method was quasi-experimental with pretest-posttest design. The statistical population of the study consisted of all second high school gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The results demonstrated that emotion regulation training improves rumination, life satisfaction, and self-esteem in mothers of children with intellectual-developmental disabilities. These findings are consistent with the previous research (Abolghasemi & Baigi, 2011;Amin et al, 2020;Karami et al, 2019;Narimani et al, 2013;Rezvan et al, 2006). It can be explained that mothers of children with special needs experience more shame, deprivation, as well as stress and depression compared to mothers of typically developing children due to the unique connection between mothers and their children, making them highly sensitive to their children's issues; thus, the children's problems become a significant source of the mothers' mental health or lack E-ISSN: 3041-8515 thereof.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The results demonstrated that emotion regulation training improves rumination, life satisfaction, and self-esteem in mothers of children with intellectual-developmental disabilities. These findings are consistent with the previous research (Abolghasemi & Baigi, 2011;Amin et al, 2020;Karami et al, 2019;Narimani et al, 2013;Rezvan et al, 2006). It can be explained that mothers of children with special needs experience more shame, deprivation, as well as stress and depression compared to mothers of typically developing children due to the unique connection between mothers and their children, making them highly sensitive to their children's issues; thus, the children's problems become a significant source of the mothers' mental health or lack E-ISSN: 3041-8515 thereof.…”
Section: Discussionsupporting
confidence: 94%
“…Emotion regulation training means reducing and controlling negative emotions and positively using emotions (Abolghasemi & Baigi, 2011). Numerous studies show the positive effects of emotion regulation training on improving various psychological variables in samples of parents of children with special needs (Karami et al, 2019;Rezvan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations